Green Buildings in Use Post Occupancy Evaluations - Watson, Chris (PEB Exchange, Programme on Educational Building, 2007)
This article briefly describes users' experiences of two "green" education buildings. It goes on to conclude that stakeholders' negotiation of building performance is necessary to minimise environmental impact, just as it is necessary to achieve other aspects of building performance